Arthur Rose. Literary Cynics: Borges, Beckett, Coetzee. Bloomsbury, 2017. - Peter Faziani (Studies in 20th & 21st Century Literature, 2019)
Review of Arthur Rose. Literary Cynics: Borges, Beckett, Coetzee. Bloomsbury, 2017. 190 pp.
Keywords: Arthur Rose; Literary Cynics; Borges; Beckett; Coetzee